The Hydropower in Ukraine: Organizational and Economic Instruments of Stimulating the Green Energy Development and Rational Use of Hydropower Potential - Hnedina, Kateryna; Nahornyi, Pavlo (Видавництво Львівської політехніки, 2022)
The article focuses on the research of hydropower in Ukraine: its current state, problems, possible ways to solve them and prospects for development. The relevance of this research refers to the importance of a comprehensive study of hydropower in Ukraine as the main component of green energy, as well as the potential for the development of hydropower in the conditions of the future post-war rebuilding of Ukraine. The main research goal is to define a complex of organizational and economic instruments to stimulate the development of hydropower in Ukraine and to ensure the rational use of hydropower potential. The core research methods are analysis, comparison, systematic approach, dialectical method, methods of abstraction and concretization, mathematical and statistical methods, etc. The terminological content of the concept and peculiarities of use and protection of water resources are characterized. The growth of their scarcity for household and agro-industrial needs of Ukraine is shown. The peculiarities of the development of hydropower as a branch of energy, which provides a principle of operation based on the use of water energy, have been studied. Weak and strong points, opportunities, and threats to the development of hydropower have been identified. The main prospects for the development of the hydropower industry in Ukraine are analyzed. All possible aspects of development are divided into two groups: effective environmental management of water bodies and costeffective environmental use of hydropower potential. Each of these areas is analyzed in the context of state policy and water policy of the largest representative of the hydropower industry. The main recommendations for the development of hydropower in Ukraine are offered, aimed at solving the problems of water management and economically justified environmental use of the hydropower potential of Ukraine.
Keywords: water resources; hydropower; hydropower potential; water policy; green energy; alternative energy sources